The Role Of Restaurant Taxes On Regional Income Of Cirebon City - Fara Azah Kharisma; Desi Rusita Nur Umaroh; Galih Wicaksono; Resvi Inayah; Edy Wahyudi (Journal of Law, Administration, and Social Science, 2023)
Cirebon City is a city located in the eastern part of West Java Province which has great natural, culinary and religious tourism potential. Judging from its tax potential, Cirebon City has quite large restaurant tax potential. This is due to the strategic geographical location of Cirebon City. Cirebon City itself is the trade center for Region III Cirebon, namely Kuningan Regency, Cirebon Regency and Indramayu Regency. Cirebon City Restaurant Tax is regulated in Cirebon City Regional Regulation Number 3 of 2019 concerning the Second Amendment to Cirebon City Regional Regulation Number 3 of 2012 concerning Regional Taxes. The regional regulations explain that Restaurant Tax is a tax levied on every service provided by a restaurant. Restaurant tax is one component of Regional Original Income (PAD) revenue. This research aims to analyze the effectiveness and contribution of Restaurant Tax to local revenue. The method used in this research is a quantitative descriptive method, by analyzing the level of effectiveness and contribution of Cirebon City Restaurant Tax revenue from 2019-2021, using secondary data obtained from pages managed by the Cirebon City Regional Revenue Agency (Bapenda). The research results show that the level of effectiveness of Restaurant Tax revenue fluctuates greatly due to the impact of the Covid-19 pandemic, and the contribution to PAD is still relatively low.